(untitled) (Journal of Information Technologies in Education (ITE), 2009)
The use of untraditional forms of conducting the studies is favourable for the personal interest in the study of subject, develops creative independence of students, trains to work with the different sourcesof knowledge.Such forms of conducting the studies diversify traditional teaching character, are instrumental in the revival of .We can see such forms as debates, cross-words, scientific essay, , business games in the article.